Response of Cold-Tolerant Aspergillus spp. to Solubilization of Fe and Al Phosphate in Presence of Different Nutritional Sources. (4th March 2013) - Rinu, K.; Malviya, Mukesh Kumar; Sati, Priyanka; Tiwari, S. C.; Pandey, Anita
Abstract : Three species of Aspergillus, namely, A. niger, A. glaucus and A. sydowii, isolated from soil samples collected from the Indian Himalayan Region (IHR), have been investigated for solubilization of aluminium phosphate and iron phosphate in the presence of different carbon and nitrogen sources. Preference of each fungal species varied for nitrogen and carbon sources, in terms of phosphate-solubilization. Among three species, Aspergillus niger gave the best results; it solubilized 32% and 8% of the supplemented aluminium phosphate and iron phosphate, respectively. The results indicated that the effect of carbon and nitrogen sources can influence the phosphate solubilizing efficiency of all the three Aspergillus spp. tested. All the three species were found to be plant-growth promoters in bioassays conducted under greenhouse conditions. The Al and Fe phosphate solubilization efficiency, investigated in the present study, is at the lower end of their previously reported tricalcium phosphate solubilization efficiency. The cultures are likely to have better field applications in agrobiotechnology, due to their potential towards solubilization of Al and Fe phosphates, which are known to have lower solubility through microbial activity.